Teacher Professionalism Development Strategy through ChatGPT Support in the Context of Education Management - Siminto; Lisnawati, Sri Dewi; Muharam, Suhari (ADMAN: Journal of Contemporary Administration and Management, 2023)
Teachers have a key role in the education system. They are responsible for providing quality education to students, which impacts on the development of individuals, communities and nations. Therefore, improving teacher professionalism is essential in efforts to improve the quality of education. The purpose of this study is to analyse strategies for developing teacher professionalism through ChatGPT support in the context of education management. It involves an investigation of the literature using a qualitative approach, which entails the assessment and interpretation of data and written materials originating from diverse sources. The conclusion of the strategy of developing teacher professionalism through ChatGPT support in the context of education management is that the utilisation of artificial intelligence can be a very useful tool in advancing the quality of education. ChatGPT can provide quick access to information, training recommendations, and even collaboration in teaching planning. However, it is important to remember that teachers still play a key role in education, and ChatGPT should only be used as a support tool. Therefore, in implementing this strategy, there needs to be clear policies and guidelines to ensure the appropriate use of ChatGPT.